2021
DOI: 10.1021/acs.nanolett.0c04614
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Ultrafast Electron Transfer Processes in Semiconductor–Metal Hybrid Nanoparticles: Toward Excitonic–Plasmonic Light Harvesting

Abstract: Recently, it was demonstrated that charge separation in hybrid metal–semiconductor nanoparticles (HNPs) can be obtained following photoexcitation of either the semiconductor or of the localized surface plasmon resonance (LSPR) of the metal. This suggests the intriguing possibility of photocatalytic systems benefiting from both plasmon and exciton excitation, the main challenge being to outcompete other ultrafast relaxation processes. Here we study CdSe-Au HNPs using ultrafast spectroscopy with high temporal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 54 publications
6
37
0
Order By: Relevance
“…The Δ A dip peak position agrees with the exciton bleach (XB) signal of the CdSe NRs (560 nm) when the NRs are directly photoexcited at 400 nm (Figure c). The XB signal is known to originate from the state-filling effect of photogenerated electrons in the CB of CdSe NRs, ,,, whose amplitude scales linearly with the average number of excitons per NR under low-exciton conditions. Control experiments (Figure S11) show that under the same 1150 nm excitation fluence, the XB signal amplitude in CdSe NR samples of a similar concentration is <2% that of the signal observed in Cu 2– x Se–CdSe, indicating the negligible contribution of two-photon absorption (TPA) of free CdSe NRs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Δ A dip peak position agrees with the exciton bleach (XB) signal of the CdSe NRs (560 nm) when the NRs are directly photoexcited at 400 nm (Figure c). The XB signal is known to originate from the state-filling effect of photogenerated electrons in the CB of CdSe NRs, ,,, whose amplitude scales linearly with the average number of excitons per NR under low-exciton conditions. Control experiments (Figure S11) show that under the same 1150 nm excitation fluence, the XB signal amplitude in CdSe NR samples of a similar concentration is <2% that of the signal observed in Cu 2– x Se–CdSe, indicating the negligible contribution of two-photon absorption (TPA) of free CdSe NRs.…”
Section: Resultsmentioning
confidence: 99%
“…However, there exists a substantial component (∼30%) of injected carriers in CdSe CB with along lifetime of ∼129 ps (Figure c), which is significantly different from metal–semiconductor plasmonic heterostructures. HET studies in Au-CdSe , and Au-CdS have shown that the lifetime of separated hot-carriers is within a couple of picoseconds due to the large density of empty states of the metal at energies near and below the semiconductor CB. Herein, the CB edge of CdSe is within the bandgap of Cu 2– x Se, where the absence of acceptor states in Cu 2– x Se may slow the backward electron recombination.…”
Section: Discussionmentioning
confidence: 99%
“… 94 Decay kinetics in the same timescale as the M. thermoacetica –CdS hybrid was reported in a hybrid metal–semiconductor nanoparticle system consisting of CdSe–Au. 117 However, lifetimes reported in the range of nanoseconds were found in Fe–Fe H 2 ase–CdS systems, 118 possibly owing to hydrogen bonding, solvent effects, and charge transfer barriers. From the evidence gathered via TA and TRIR spectroscopy, two proposed pathways for charge and energy transfer were proposed: the non-H 2 ase-mediated pathway in glucose incubated cells and the membrane-bound H 2 ase mediated pathways in H 2 incubated cells.…”
Section: Elucidation Of Electron Transfer Mechanisms and Microbial Li...mentioning
confidence: 99%
“…By using ultrafast spectroscopy, along with high temporal resolution and near-infrared excitation, the plasmon-induced charge transfer (PICT) pathway was resolved, and it was discovered that hot-electron transfer to CdSe occurred in the timescale of fewer than 30 femtoseconds, whereas back transfer from the semiconductor to the metal was found to be within 210 fs. 117 To compete with the extremely fast back-transfer to the metal, extraction of the electrons needs to be greater than the rate of back-transfer. This issue needs to be realised when designing hybrid systems to avoid inefficient and undesired transfer pathways.…”
Section: Elucidation Of Electron Transfer Mechanisms and Microbial Li...mentioning
confidence: 99%
“…Metamaterials have been widely studied due to their outstanding capacities in manipulating electromagnetic waves, such as imaging, color filter, plasmonic structure color, surface-enhanced Raman scattering, sensing, light absorption switches, energy harvest, and thermal emitters. [20][21][22][23][24][25][26][27] Several metamaterial-based structures have been proposed to realize radar-infrared compatible camouflage. [18,19,[28][29][30][31][32][33][34][35] The kernel idea to achieve the compatible camouflage is to cover a broadband microwave absorber (MA) with an infrared shielding and microwave transparent layer.…”
mentioning
confidence: 99%